MORAL EDUCATION IN PRIMARY SCHOOLS WITH A STORYTELLING APPROACH - Adnyani, Ni Ketut Sari; Landrawan, I Wayan (Center of Language and Cultural Studies, 2021)
The purpose of this study was to analyze moral education on moral education in elementary school children with a storytelling approach. This study used an experimental design in testing moral education in elementary school children with a storytelling approach. The instruments used to collect data in this study were questionnaires, learning outcomes tests, score inventory and self-evaluation. The questionnaire was designed to determine the feasibility of moral education instruction. The learning outcome test is used to find out the score. Data analysis used multivariate analysis of variance. The results showed that there was a significant difference after storytelling on moral development (t = 3.478 and p = 0.006 (p <0.05). Thus, it can be concluded that storytelling can improve the moral development of elementary school students in Karangasem Regency. .